The interactive effect of the application of accreditation standards (JCIs) and the practice of administrative control in improving the quality of health services: a study on Yemeni hospitals - Ammar Ali Alraimi; Murad Mohammed Al-Nashmi (BMC Health Services Research, 2024)
Abstract Background This study aimed to examine the interactive effect of applying JCI accreditation standards and administrative control in improving the quality of health services in Yemeni hospitals. By examining the synergistic relationship between these two components, this study sought to shed light on how hospitals can improve their performance and achieve sustainable advancements in healthcare quality. Methods This study utilized a quantitative research design and collected data from Yemeni hospitals. The sample size was determined via the Krejcie and Morgan table, which provides a recommended sample size on the basis of the population. A total of 310 healthcare professionals were selected through a random sampling technique. Hypotheses were formulated to examine the impact of JCI accreditation standards and administrative control on healthcare quality. Statistical analyses were also conducted to test these hypotheses and determine the interaction effect between the two variables. Results The results confirmed that applying JCI accreditation standards has a statistically significant positive effect on improving the quality of health services in hospitals. Additionally, the practice of administrative control had a statistically significant effect on healthcare quality. Furthermore, there was an interactive effect between the application of JCI accreditation standards and administrative control, indicating that their combined implementation led to even greater improvements in healthcare quality. Conclusion The significance of this study lies in its potential to inform healthcare policymakers, administrators, and practitioners about the importance of integrating accreditation standards with robust administrative control measures. The findings emphasize the need for hospitals to prioritize both the implementation of accreditation standards and the establishment of effective administrative control systems to ensure the delivery of high-quality healthcare services. This study contributes to the literature by highlighting the interactive impact of these factors and providing insights into their synergistic relationship.